THE COMMERCIALISATION OF KNOWLEDGE MANAGEMENT PRACTICES TO K-BASED DEVELOPMENT IN MALAYSIA (Journal of Information and Communication Technology, 2008)
This paper studies the connection between the commercialization of knowledge management practices and its contributions toward the knowledge-based development in Malaysia. Theoretical relations in this paper were tested through an empirical study carried out among public-listed organisations in the industrial products, consumer products, and service industries in Malaysia. The findings of this paper revealed that it is important for corporations to focus on knowledge management in the development of the organisation’s corporate strategy. Empirical evidence supported the view that firms with knowledge management capabilities and understanding will utilise these capabilities to drive their quality strategy, thus performing better than those that do not. In addition, the finding serves as an initial move among private sector business toward a knowledge-based country. This paper concludes that these practices have a positive incidence not only on the performance of the firm but it also gives some initial contributions toward the development of Malaysia as a knowledge-based country.